Persaingan Politik dan Anggaran Kesehatan: Telaah Nilai Keadilan Distribusi dalam Ekonomi Islam - Inayah, Siti; Ekawati, Evi; Hasimi, Diah Mukminatul (Kartika: Jurnal Studi Keislaman, 2025)
The purpose of the study is to understand the influence of political economy competition on government health budget allocation in Indonesia and the relationship between the influence of political economy competition on the health budget with the Islamic Economic Perspective. The Indonesian Democracy Index (IDI), Population Growth (PP), and poverty rate are the variables used. Panel data regression analysis with Random Effect (REM) model is the research method. The findings show that intensified political competition negatively affects health budget allocation, with a coefficient value of -0.033 on the IDI variable and -0.014 on the PP variable. Meanwhile, poverty level has a positive influence on health budget with a coefficient of 0.195. The Chow test shows a probability value of 4.656e-127, which indicates that the model fit is Random Effect. The Hausman test results show a probability value of 0.188, which supports the selection of the Random Effect model. In addition, the Breusch-Pagan value of 805,833 is shown in the Lagrange Multiplier (LM) test, with a probability of 0.000, which also indicates that the appropriate model is Random Effect. The implications of this study show the importance of more equitable policies in health budget allocation, by giving more attention to poor regions and reducing the impact of imperfect political competition.